Evaluation of anti-proliferative activity of Eryngium caucasicum on melanoma cancer cells - Haleh Forouhandeh; Zahra Rezaei Param; Ommoleila Molavi; Parina Asgharian; Vahideh Tarhriz (BMC, 2022)
Abstract Background The genus Eryngium is a member of the Apiaceae family that has shown different pharmacological effects mainly including anti-inflammatory, analgesic, anti-cancer, hepatoprotective, and anti-oxidant. Previous research on the anti-cancer activity of Eryngium in some cancer cell lines has led us to explore the anti-proliferative activity of E. caucasicum in the B16F10 cell line. Objective In this study, the antiproliferative activity of E. caucasicum on melanoma cancer cells (B16F10) and non-cancerous cells (HFFF2) were evaluated in vitro. Methods The dried plant sample of E. caucasicum was extracted by Soxhlet apparatus with n-Hexane, dichloromethane, and methanol solvents. The effects of cytotoxicity of the extracts by the MTT method on melanoma cancer cells (B16F10) and noncancerous cells (HFFF2) was investigated for 24 and 48 hours. Then, the cytotoxicity of different fractions of the strong extract against normal and cancer cells was evaluated by this method. Annexin V/PI assay was used to study the induction apoptosis via the fractions in cancer cells. Findings According to the results of the MTT test, n-Hexane extract is the most effective extract against the B16F10 cell line and is a candidate for fractionation with VLC. Among the fractions, 40 and 60% VLC fractions of n-Hexan extract inhibited the growth of B16F10 cells at 24 and 48 hours while, these fractions at IC50 concentration had no cytotoxic effects on normal cells. Treatment of cancer cells with effective extract caused apoptosis and necrosis and 40 and 60% more fractions induced apoptosis in these cells. Conclusion The n-Hexane extract of E. caucasicum and its 40 and 60% fractions showed the highest cytotoxic effect against the B16F10 cell line compared to other extracts and control groups. This inhibition was made through induction of apoptosis.